Analisis Pengaruh Pengolahan Transaksi Penjualan terhadap Kualitas Informasi Akuntansi Penjualan Diperusahaan Dagang - Ade Andriana Salsabila; Rayyan Firdaus (Profit: Jurnal Manajemen, Bisnis dan Akuntansi, 2024)
Effective sales transaction processing influences the quality of the accounting information produced, which ultimately can support better managerial decision making in the company. The research aims to analyze the influence of sales transaction processing on the quality of sales accounting information in companies. Using quantitative methods, data was collected through surveys distributed to related parties in the company's sales accounting process. The variables analyzed include accuracy, timeliness and completeness of information produced by the sales transaction processing system. The research results show that good sales transaction processing, which involves proper recording and the use of reliable information systems, has a significant positive influence on the quality of sales accounting information. These findings indicate that improving transaction processing increases the quality of accounting information, which ultimately contributes to the efficiency and effectiveness of company management.